Validating Modified-ANT and Stroop Tests for Diagnosing Minimal Hepatic Encephalopathy (MHE) Patients in the Pakistani Population - Ihsan, Saniya; Asim, Mnahil; Zahra, Rida; Ali, Danish; Ihsan, Bismah; Akhter, Tayyab Saeed; Imran, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Minimal Hepatic Encephalopathy (MHE) is a subclinical cognitive impairment affecting a substantial proportion of patients with chronic liver disease (CLD). Early diagnosis remains challenging in resource-limited settings like Pakistan, where standard neuropsychological testing is not widely accessible. This study aimed to validate the Modified Animal Naming Test (ANT) and the Stroop Test as simplified tools for MHE screening in the Pakistani population. Methods: A case-control study was conducted at Holy Family Hospital, Rawalpindi, enrolling 196 participants—98 patients with CLD and 98 age- and gender-matched healthy controls. Participants underwent cognitive assessment using three psychometric tools: Psychometric Hepatic Encephalopathy Score (PHES), Modified ANT, and a smartphone-based Stroop Test. A PHES score ≥ -5 was considered diagnostic for MHE. ANT scores <14 and Stroop completion times >190 seconds were also indicative of MHE. Associations among test results and demographic variables were analyzed using SPSS version 26, with p < 0.05 considered statistically significant. Results: The Modified ANT was completed by all participants and revealed MHE in 51% of patients. PHES confirmed MHE in 31.6% of patients. A statistically significant association was found between Modified ANT and PHES scores (p < 0.001). Stroop Test completion was low, with only 8.2% of patients able to perform it, highlighting barriers related to low education and IT literacy. PHES was also significantly associated with age (p < 0.001) but not with gender or education level. Conclusion: The Modified ANT is a reliable and culturally appropriate tool for MHE screening in Pakistani patients with CLD, showing strong correlation with PHES. The Stroop Test, though theoretically valuable, demonstrated limited applicability due to educational and technological constraints. Incorporating low-literacy-friendly psychometric tests like the Modified ANT into routine hepatology practice can facilitate early diagnosis of MHE and help mitigate progression to overt hepatic encephalopathy.